Perpindahan Massa Yang Disertai Dengan Reaksi Kimia Sistem Cair-Cair Yang Tidak Saling Melarut Pada Reaksi Hidrolisis Bensoil Khlorid = Mass Transfer and Chemical Reaction in Liquid-Liquid System in Benzoyl Chloride Hidr - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Mass transfer followed by chemical reaction is widely used in chemical industries, such as reactive extraction process and hydrolysis of organic halogen. In process design, information on chemical compounds interacting in the system must be known. Important information for the scheme of process is the characteristic of mass transfer and reaction. The values of mass transfer coefficient and reaction rate constant are used to support the appropriate mathematical approach for liquid-liquid system. The values are also applicable to determine the regime controlling the system. The experiment was conducted by mixing benzoyl chloride and water with a certain ratio in a three necks flash equipped with a cooler, agitator, and conductometer. Every 40 second, the conductivity was measured until stable conductivity was reached. This value was converted to HO concentration with a standard curve made before. By analyzing the regime on the curve obtained, the value of reaction rate constant (k') was obtained at the chemical regime at the initial period and the value of mass transfer coefficient (kLao) was obtained at the dynamic regime at the last period. The reaction rate constant (k') was independent on agitation speed and reactant ratio, but dependented on temperature. The relation between k' and temperature can be approximated by the equation: = 19.015 -7624.8 / T with average deviation of 15.85%. The relation between mass transfer coefficient and agitator speed can be represented by Sherwood, Reynolds, and Schmidt number with the equations: benzoyl chloride - water ratio = 5:250 Sh = 36.5 Re 0.86 Sc 1/ 3 benzoyl chloride - water ratio = 2.5:250 Sh = 20.45 Re 0-87 Sc 1/ 3 benzoyl chloride - water ratio = 0.5:250 Sh = 2.3 Re C-86Sc 1 / 3 with average deviation is 15.28 -16.95%.